The system of long-term care in the Czech Republic - Agnieszka Sowa (Center for Social and Economic Research (CASE), 2010)
Developing responsive to needs, efficient and sustainable long-term care systems for elderly becomes due to rising demographic pressures an urgent issue all over Europe. Czech Republic is among the countries that have redesigned long-term care system according the principles of accessibility, quality and fiscal tenacity in the past couple of years. The reform process was well rooted in the practice of local governments and social sector empowering institutions that existed before 2006, when the reform was introduced, but were insufficiently anchored in legal regulations. The newly established long term care system covers a wide spectrum of services, from cash benefits to dependent in need via different types of social services and institutional care. Still, similarly to other countries of the Central and Eastern Europe region long care is disintegrated between the social system and health care which also is responsible for some types of institutional establishments. The system is also not free from critique for the lack of formal definition of long term care, lack of integration of services, their shortage and poor quality. Thus despite state efforts, the care over elderly remains family responsibility and state support is not always sufficient.
Keywords: H51; H55; I18; 330; long-term care; health system care; social services; Czech Republic; Langzeitpflege; Sozialer Dienst; Gesundheitswesen; Sozialpolitik; Tschechien